The Imperative of Request of Indonesian and Japanese Language: A Comparative Studies on Politeness - Rachman, Zulfikar (Lingua Cultura, 2022)
The research aimed to find the imperative of requests and their politeness in the Indonesian and Japanese languages. It also aimed to analyze the similarities and dissimilarities between both languages. The method applied in the research was comparative studies. The data on both languages were collected from novels, movie dialogue, email, questionnaires, SNS (LINE, WhatsApp, Instagram, Facebook), and daily conversation corpus. As a result, the request markers "tolong" and "mohon" change an imperative into requesting expression. "Boleh" and "bisa" are necessary to construct an interrogative imperative of request. On the other hand, in the Japanese language, there are onkei hyōgen (~te kureru/~te kudasaru/~te morau/~te itadakeru) and ganbō hyōgen (~tai, ~te hoshii). It also has positive (masu), negative (nai/masen), assertive (masuka/desuka), and tentative (deshōka) forms. In the Indonesian and Japanese languages, commanding has the lowest politeness, followed by requesting expression. The permission request is the politest. Also, the imperative of request shows modesty and does not strongly force the audience. The imperative of request in the Indonesian language is a command that got request markers "tolong" and "mohon" to soften the command intention. On the contrary, the Japanese separate the imperative of command and request forms.